Modele wewnętrzne jako alternatywna forma wyznaczania kapitału wypłacalności zakładów ubezpieczeń - klasyfikacja modeli - Kurek, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The principles of Solvency II facilitate the application of internal models in order to define the actual demand for guarantee capital by insurance institutions. The article presents the concept of their application and the theoretical (academic) classification of these models which may be used by insurance institutions for both their own needs as well as the needs of supervisory authorities. The characterized classification criteria cover as follows: the entity developing the model, considered time span, model's complexity, the complexity of organization structure in an insurance group, model's advancement stage, the timing of model analysis, modeling instruments, the level of included risks specification, correlation between risks included in the model as well as the way of an overall risk aggregation. The presented classification was developed based on the analysis of models' practical application by some insurance companies (which apply models for their own needs) but also theoretical solutions, therefore it may be of assistance for both insurance institutions as such (which have not been applying them yet) and supervisory authorities (which are in the process of getting ready for their approval). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 215-224